2008
DOI: 10.1177/0145482x0810200705
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Comprehension of Synthetic Speech by Students with Visual Impairments: The Case of Similar Acoustic Patterns

Abstract: This study examined the perceptions held by sighted students and students with visual impairments of the intelligibility and comprehensibility of similar acoustic patterns produced by synthetic speech. It determined the types of errors the students made and compared the performance of the two groups on auditory discrimination and comprehension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…The agreement between these two transcriptions was high (r ¼ 0.87, p 5 .01). Error responses were categorized based on phoneme error patterns (see also Papadopoulos et al, 2008) that were considered phonological in that the error resulted in a change in the auditory representation of the word.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The agreement between these two transcriptions was high (r ¼ 0.87, p 5 .01). Error responses were categorized based on phoneme error patterns (see also Papadopoulos et al, 2008) that were considered phonological in that the error resulted in a change in the auditory representation of the word.…”
Section: Methodsmentioning
confidence: 99%
“…Papadopoulos, Argyropoulos, and Kouroupetroglou (2008) examined intelligibility and comprehensibility performance of students with and without visual impairments who were asked to repeat acoustic patterns produced by synthetic speech. The participants with visual impairments responded correctly significantly more frequently than their sighted peers.…”
Section: Introductionmentioning
confidence: 99%
“…The discrimination, perception and comprehension of synthetic speech (used in Digital Talking Books) by visually impaired students has been already studied [34][35][36].…”
Section: Book Production In Alternative Accessible Formatsmentioning
confidence: 99%
“…It has been shown that blind individuals obtain higher intelligibility scores when compared to sighted individuals (Hugdahl et al, 2004) and that this benefit is also observed for the intelligibility of synthetic speech (Papadopoulos et al, 2008;Pucher et al, 2010a) possibly due to the familiarity effect (Barouti et al, 2013) as blind individuals are exposed to the material more through the use of screen readers and audio books. It was also shown repeatedly that blind individuals show a much higher intelligibility for fast synthesised speech (Moos and Trouvain, 2007;Pucher et al, 2010a), an effect that can be found for a wide range of synthesisers: formant, diphone, unit selection and Hidden Markov Model (HMM) based (Syrdal et al, 2012).…”
Section: Introductionmentioning
confidence: 99%